Pemberdayaan Mahasiswa dalam Kampanye Kesehatan Mental melalui Pelatihan Produksi Media - Noor Afy Shovmayanti; Farid Aji Prakosa; Dani Kurniawan; Khusnul Amalin (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Mental health has an impact on well-being both physically and socially. Mental health has become a serious problem and has received special attention especially at the age of high school and higher education due to the high rate of mental health disorders at that age. Mental health disorders or depression is a psychiatric problem that is prone to occur in adolescents. Data in Indonesia shows that 6.1% of the Indonesian population aged 15 years and over experience mental health disorders. Mental health disorders can be prevented. Preventive action is to provide knowledge and awareness to the community, one of which is through a campaign on social media using video media. Campaign techniques through media using cool and unique content so that information can be easily conveyed clearly and accepted by the public. Video planning and production training is considered relevant to the creativity and media consumption used in generation Z students.